2015
DOI: 10.1016/j.febslet.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

High‐methionine diets accelerate atherosclerosis by HHcy‐mediated FABP4 gene demethylation pathway via DNMT1 in ApoE−/− mice

Abstract: a b s t r a c tHomocysteine (Hcy) is an independent risk factor for atherosclerosis, but the underlying molecular mechanisms are not known. We investigated the effects of Hcy on fatty acid-binding protein 4 (FABP4), and tested our hypothesis that Hcy-induced atherosclerosis is mediated by increased FABP4 expression and decreased methylation. The FABP4 expression and DNA methylation was assessed in the aorta of ApoE À/À mice fed high-methionine diet for 20 weeks. Over-expression of FABP4 enhanced accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 39 publications
5
66
0
Order By: Relevance
“…In the present study, it was also found that B1 repetitive elements exhibited hypomethylation in the blood cells of the AS model. FABP4 has been identified as a potential circulation marker for metabolic syndrome, and is increased in individuals with diabetes and metabolic syndrome due to the development of subclinical inflammation, which leads to AS (44). The present study is the first, to the best of our knowledge to report that the methylation levels of FABP4 were closely associated with AS.…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, it was also found that B1 repetitive elements exhibited hypomethylation in the blood cells of the AS model. FABP4 has been identified as a potential circulation marker for metabolic syndrome, and is increased in individuals with diabetes and metabolic syndrome due to the development of subclinical inflammation, which leads to AS (44). The present study is the first, to the best of our knowledge to report that the methylation levels of FABP4 were closely associated with AS.…”
Section: Discussionsupporting
confidence: 49%
“…Very recently, it has been reported that the ratio between SAM/SAH should be used as a biomarker and may provide a sensitive indicator for the clinical diagnosis of atherosclerosis [74]. Another scientific group investigate the effect of elevated Hcy level on fatty acid binding protein 4 (FABP4) [75]. Their results showed that FABP4 has a very important function in lipid metabolism disturbance after Hcy treatment and also that DNA methyltransferase 1 (DNMT1; EC 2.1.1.37) could be a potential therapeutic target in Hcy-related atherosclerosis [75].…”
Section: Hyperhomocysteinemia and Diseasesmentioning
confidence: 99%
“…Another scientific group investigate the effect of elevated Hcy level on fatty acid binding protein 4 (FABP4) [75]. Their results showed that FABP4 has a very important function in lipid metabolism disturbance after Hcy treatment and also that DNA methyltransferase 1 (DNMT1; EC 2.1.1.37) could be a potential therapeutic target in Hcy-related atherosclerosis [75]. …”
Section: Hyperhomocysteinemia and Diseasesmentioning
confidence: 99%
“…Previous reports have demonstrated that elevated levels of Hcy have been associated with a number of disease states, including AS (18,19). Despite the important contribution of Hcy to accelerated AS, the specific molecular mechanisms in response to Hcy within macrophages, which is important in atherogenesis, remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%